Secondary analyses for genome‐wide association studies using expression quantitative trait loci. Issue 3 (21st March 2022) - Ngwa, Julius S.; Yanek, Lisa R.; Kammers, Kai; Kanchan, Kanika; Taub, Margaret A.; Scharpf, Robert B.; Faraday, Nauder; Becker, Lewis C.; Mathias, Rasika A.; Ruczinski, Ingo
Abstract: Genome‐wide association studies (GWAS) have successfully identified thousands of single nucleotide polymorphisms (SNPs) associated with complex traits; however, the identified SNPs account for a fraction of trait heritability, and identifying the functional elements through which genetic variants exert their effects remains a challenge. Recent evidence suggests that SNPs associated with complex traits are more likely to be expression quantitative trait loci (eQTL). Thus, incorporating eQTL information can potentially improve power to detect causal variants missed by traditional GWAS approaches. Using genomic, transcriptomic, and platelet phenotype data from the Genetic Study of Atherosclerosis Risk family‐based study, we investigated the potential to detect novel genomic risk loci by incorporating information from eQTL in the relevant target tissues (i.e., platelets and megakaryocytes) using established statistical principles in a novel way. Permutation analyses were performed to obtain family‐wise error rates for eQTL associations, substantially lowering the genome‐wide significance threshold for SNP‐phenotype associations. In addition to confirming the well known association between PEAR1 and platelet aggregation, our eQTL‐focused approach identified a novel locus (rs1354034) and gene (ARHGEF3) not previously identified in a GWAS of platelet aggregation phenotypes. A colocalization analysis showed strong evidence for a functional role of this eQTL.